The Existence Of The Karakasangrahah Lontar As A Guide To Karakam In Sanskrit Grammar - I Wayan Gama (International Journal Labs, 2024)
The existence of the Sanskrit language which is so amazing with its various scholarships, both Paravidya and Aparavidya, has made a major contribution to world culture and the archipelago. In Bali, Karakam's knowledge is written in a horizontal sheet, with the title Lontar Karakasangrahah, which until now has only been studied by foreign researchers such as Silvain Levy and J Gonda. However, until now the general public did not know about its existence and knowledge. This qualitative research aims to identify and describe the Existence of Lontar Karakasangrahah as a Karakam Guide in Sanskrit Grammar. Primary data sources are either observations on Lontar Karakasangrahah as well as information from experts as well as secondary data both from other supporting books. Based on the results of the research and discussion, it was found that: (1) The Lontar form of Karakasangrahah consists of 21 stanzas of Karika written in Balinese script with an introduction to Sanskrit, explaining about 6 Karakam namely Karta, Karma, Karanam, Sampradanam, Apadanam and adhikaranam and sese and the relationship with use the 7 vibhaktih namely Prathamavibhaktih, Dvitayavibhaktih, Trti yavibhaktih, Caturthavibhaktih, Pañcamavibhaktih sasthavibhaktih, Saptamivibhaktih and Sambhodanam. (2) The existence of the use of Karakam is reflected in the findings of various local Sanskrit literary works in the form of Padya (sloka) and Padya (prose) found with strong Karakam compositions.